Update and extension of the Brazil SimSmoke model to estimate the health impact of cigarette smoking by pregnant women in Brazil - André Salem Szklo; Zhe Yuan; David Levy (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2017)
Abstract: A previous application of the Brazil SimSmoke tobacco control policy simulation model was used to show the effect of policies implemented between 1989 and 2010 on smoking-attributable deaths (SADs). In this study, we updated and further validated the Brazil SimSmoke model to incorporate policies implemented since 2011 (e.g., a new tax structure with the purpose of increasing revenues/real prices). In addition, we extended the model to estimate smoking-attributable maternal and child health outcomes (MCHOs), such as placenta praevia, placental abruption, preterm birth, low birth weight, and sudden infant death syndrome, to show the role of tobacco control in achieving the Millennium Development Goals. Using data on population, births, smoking, policies, and prevalence of MCHOs, the model is used to assess the effect on both premature deaths and MCHOs of tobacco control policies implemented in Brazil in the last 25 years relative to a counterfactual of policies kept at 1989 levels. Smoking prevalence in Brazil has fallen by an additional 17% for males (16%-19%) and 19% for females (14%-24%) between 2011 and 2015. As a result of the policies implemented since 1989, 7.5 million (6.4-8.5) deaths among adults aged 18 years or older are projected to be averted by 2050. Current policies are also estimated to reduce a cumulative total of 0.9 million (0.4-2.4) adverse MCHOs by 2050. Our findings show the benefits of tobacco control in reducing both SADs and smoking-attributable MCHOs at population level. These benefits may be used to better inform policy makers in low and middle income countries about allocating resources towards tobacco control policies in this important area.